Market segmentation of leisure boats exhibited in the boat show by using multivariate statistical techniques - Kılıç, Alper (Array, 2020)
The aim of this study is to segment recreational boats according to their basic parameters in order to develop marketing strategies and to investigate the benefit/cost factors in consumer preferences across segments. For this purpose, 69 recreational boats under 10 meters exhibited at the Istanbul Boat Show were clustered using basic parameters. In the study, in which hierarchical clustering and multidimensional scaling analysis were used, the boats were divided into four clusters and these results were intended to create an input in the marketing strategies of the boats. These clusters are labelled from the lowest segment to the highest segment, A, B, C and D in ascending order. Based on the calculated averages of these segments for five variables, their intended use is introduced. This segmentation provides guiding findings in different areas such as marketing, advertising and production strategies from the arrangement of the boats within the fair. In addition, alternative actions have been determined for both the customer and the seller by revealing the costs to be incurred in the event that customers prefer different segments.